Analisis Kondisi Sarana Prasarana Pendidikan (Studi Kasus SDN 03 Sadahayu, Majenang Cilacap) - Tri Angkarini; Ricky Eka Sanjaya; Feni Arifiani; Ulfah Ridhwan Dirham; Nini Adelina Tanamal (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2026)
The educational facilities and infrastructure at SDN 03 Sadahayu, Majenang, face serious challenges due to building damage and a lack of supporting facilities, exacerbated by its location in a mountainous area with difficult road access. The purpose of this study was to analyze the impact of limited facilities and infrastructure on the teaching and learning process and to understand the experiences of teachers and students in this situation. A phenomenological approach was used as the primary method, with data collected through observation, interviews, and documentation of teachers, students, and the school's physical facilities. The sample included all teaching staff and active students during the study. The results showed that limited classroom space, laboratories, sports facilities, and sanitation and religious facilities significantly affected teachers' learning motivation and students' learning experiences. Extreme geographic conditions slowed access and exacerbated these obstacles. Discussions led to the need for infrastructure improvements and community empowerment as key strategies to ensure educational sustainability. The conclusions affirmed the urgency of improving facilities to support optimal learning processes and improve the well-being of students in isolated areas.